Genesis : the Creation and the Flood [videorecording (DVD)] - Olmi, Ermanno, 1931-2018; Scofield, Paul, 1922-2008; Antonutti, Omero, 1935-2019 (Bible collection., 2020)
Dramatization of the key stories in the Book of Genesis, including Adam and Eve in Paradise as they are tempted by the snake, the trials of Cain and Abel as Cain is driven to murder his brother, and the epic story of Noah and the Ark where Noah is commanded by God to save two of every creature from the land.